CLINICAL AND GENETIC HETEROGENITY OF JUVENILE MYOCLONIC EPILEPSY - N. A. Shnayder; O. S. Shilkina; K. V. Petrov; I. A. Chernykh; A. V. Diuzhakova (Эпилепсия и пароксизмальные состояния)
The idiopathic generalized epilepsies constitute roughly one-third of all epilepsies. Juvenile myoclonic epilepsy (Janz syndrome) is characterized by myoclonic jerks on awakening, generalized tonic-clonic seizures, and typical absences, with the latter occurring in more than one-third of the patients. However, typical absences are not the predominant seizure type, and are usually very mild and simple (with no automatisms or localized limb jerks). Juvenile myoclonic epilepsy usually appears in adolescents between 12 and 18 years old. Half of patients with this condition have relatives with epilepsy. The genetic basis of this syndrome is complex and the mechanism of transmission is unclear. It is possible that several different genes are responsible. The authors presented the review of results modern clinical and genetic studies of juvenile myoclonic epilepsy. Information obtained from this review strongly suggests a heritable condition that merits further investigation.